Long-Term Anticoagulation in Secondary Ischemic Stroke Prevention: The Prospective Multicenter RESTAIC Registry - Gutiérrez-Zúñiga, Raquel; Rigual, Ricardo; Torres-Iglesias, Gabriel; Sánchez-Velasco, Sara; Alonso de Leciñana, María; Masjuan, Jaime; Álvarez Velasco, Rodrigo; Navas, Inmaculada; Izquierdo-Esteban, Laura; Fernández-Ferro, José; Rodríguez-Pardo, Jorge; Ruiz-Ares, Gerardo; et al. (Frontiers in Neurology, 2020)
Background and Objective Oral anticoagulation (OAC) for secondary stroke prevention is recommended in atrial fibrillation (AF) and other sources of cardioembolic stroke. Our objectives were to explore the differences in ischaemic and haemorrhagic events when using OAC for secondary stroke prevention according to the type of anticoagulant treatment and to analyse the number and reasons for OAC switches during long-term follow-up. Methods Ischaemic stroke (IS) patients who were discharged on OAC for secondary stroke prevention from January 2014 to October 2017 were recruited in a prospective, multicentre, hospital-based registry. Follow-up at three months was scheduled at the outpatient clinic with subsequent annual phone interviews for 3 years. Patients were classified into 3 study groups according to OAC at discharge: Vitamin K antagonist (VKA), Factor Xa inhibitor (FXa) or direct thrombin inhibitor (DTI). We compared stroke recurrences, intracranial haemorrhage, major bleeding and all-cause mortality during the follow-up. We recorded any switches in OAC and the main reasons for the change. Results A total of 241 patients were included. Anticoagulant was indicated in the presence of a source of cardioembolic stroke in 240 patients (99.6%) and lupus plus antiphospholipid syndrome in one patient. Up to 86 patients (35.6%) were on OAC before the index stroke; in 71 (82.5%) of them this was VKA. At hospital discharge, 105 were treated with FXa (43.8%), 96 with VKA (39.6%), and 40 with DTI (16.6%). The cumulative incidences at 3 years were 17% for stroke recurrence, 1.6% for intracranial haemorrhage, 4.9% for major haemorrhage and 22.8% for all-cause mortality, with no differences among OAC groups in any outcomes. During the follow-up, 40 OAC switches were recorded (63% of them to FXa), mostly due to stroke recurrence. Conclusion Long-term OAC in secondary stroke prevention is associated with a lower frequency of bleeding complications than stroke recurrences. No differences between anticoagulant drugs were found in any of the analysed outcomes. The main cause for OAC switch during follow-up was stroke recurrence.